The internet, consumer empowerment and marketing strategies - Pires, G.; Stanton, J.; Rita, P. (European Journal of Marketing, 2006)
Purpose - Arguing that increasing use of information and communication technologies (ICT) is shifting market power from suppliers to consumers, the ensuing consumer empowerment is presented as an unintended consequence of marketing. Marketing implications arising from this consumer empowerment are examined in terms of a process where control and management by suppliers over consumer access and enablement are increasingly difficult. Design/methodology/approach - Consumer empowerment is examined historically, using quality gap analysis to capture an ongoing power struggle between consumers and suppliers. This draws out the limitations of current marketing and management strategies. The different forms of marketing challenges in this new environment are discussed. Findings - The role of marketing strategies in fostering controlled consumer empowerment is reflected in the development of information-based consumer-centric marketing strategies that seek to enable and control delegation. In designing such strategies, consumers' familiarity with and use of ICT are both strengthened and widened, emphasising the uncontrolled nature of the consumer empowerment process. Research limitations/implications - The approach is literature-based, focussing on the ICT enabled process. It does not address the psychology of empowerment. Since, consumer empowerment may imply switching suppliers in search of better value propositions, business cannot afford to ignore it, justifying the need for further research of both elements. Practical implications - Marketing strategy rests on a control premise and the analysis of the consumer empowerment process implies that current customer-centric strategies are operating under a false premise. There is a need to regain control over the marketing process, that is, to either manage the technological empowerment of consumers, or to devise new strategies cognisant of the possibility that such technological empowerment cannot be managed. The valuation of consumer loyalty in this environment rises significantly. Originality/value - An historical perspective to consumer empowerment exposes the tensions between suppliers and consumers arising from ICT usage. A separation of consumer access and enablement from control and management by suppliers is shown to have important marketing strategy design implications.